An Introspective Enquiry Mutually Emplacing Teacher and Non-literate Former Refugee Students in Pedagogical Landscapes - Buchanan, Elizabeth Nancy (Curtin University, 2016)
Searching to discover what it is that is in the self that is brought to the teaching role this study transports the teacher along a lived experience trajectory. Assuming an interface stance as teacher-learner, researcher-interpreter, narrator-writer, to find insightful meaning the inquiry glances back as it moves forward, emplacing the teacher with adult former refugee students in an empowering landscape that engenders self-learning and respect for diversity within a culture of education.